Papyri in the Princeton University Collections, Volume II : Taxation in Egypt from Augustus to Diocletian - Kase, Edmund Harris (Book collections on Project MUSE., 2017)
The book description for the forthcoming "Papyri in the Princeton University Collections" is not yet available.